Dynamic modeling and verification of unicycle mobile robot system - Abdul Rashid, Mohd Zamzuri; Sidek, Shahrul Na'im (2011)
Unicycle mobile robot main advantages over multiwheeled mobile robot are higher degree of mobility and less space as it only has one wheel to move. The system developed consists of two parts which are the lower and the upper parts. The lower part is composed of a wheel which is moving back and forth to stabilize the pitch angle. Meanwhile, the upper part consists of a reaction disc and the main frame that functions to stabilize the roll angle of the unicycle system. The dynamic model of the unicycle mobile robot is de veloped using Lagrangian method and verified through simulation using MATLAB software. The results show that the dynamic model developed can be used to design a model-based controller.